Constraints of Artificial Intelligence Integration in the 21st Century Human Resource Management in Higher Institutions in Nigeria (International Journal of Educational Management, Rivers State University., 2025)
The integration of artificial intelligence (AI) in human resource management (HRM) has transformed the way organizations operate, but its adoption in higher institutions in Nigeria is faced with numerous constraints. The integration of AI in 21st HRM is germane in areas such as talent management, employee engagement, performance management, training and development and so on. This study identified and examined the constraints hindering the effective integration of Artificial Intelligence in the 21st century human resource management in Nigerian higher institutions. They include limited technical expertise, inadequate infrastructure, high cost of implementation, data privacy and security concerns, resistance to change from staff, limited access to funding, inadequate policy and regulatory framework, limited awareness and understanding of Artificial Intelligence benefits, dependence on manual processes, and limited availability of AI-powered human resource tools. These constraints pose significant challenges to the successful adoption of Artificial Intelligence in the 21st century Human Resource Management in Nigerian higher institutions, leading to inefficiencies, ineffectiveness, and lack of competitiveness. The study suggested strategies to address these constraints, including training and development programmes, infrastructure upgrades, cost-benefit analysis, data protection policies, change management, funding exploration, policy development, awareness creation, process automation, and collaboration with vendors. Addressing these constraints will enable Nigerian higher institutions to leverage Artificial Intelligence in Human Resource Management, enhancing their operational efficiency, effectiveness, and global competitiveness.